The Drums of Affliction: A Study of Religious Processes Among the Ndembu of Zambia - Turner, Victor W. (Clarendon, 1968)
In this study of the Ndembu of Zambia, ritual is examined under two aspects: as a regulator of social relations over time and as a system of symbols. Social life is thereby given direction and meaning. An extended case-study of a series of ritual performances in the life of a single village community is analysed in order to estimate the effects of participation in these symbolic events on its component groups and personalities.
free